Lovastatin‐induced apoptosis is mediated by activating transcription factor 3 and enhanced in combination with salubrinal. Issue 2 (1st August 2013) - Niknejad, Nima; Gorn‐Hondermann, Ivan; Ma, Laurie; Zahr, Stephanie; Johnson‐Obeseki, Stephanie; Corsten, Martin; Dimitroulakos, Jim
Abstract : We have previously demonstrated the ability of lovastatin, a potent inhibitor of mevalonate synthesis, to induce tumor‐specific apoptosis. The apoptotic effects of lovastatin were regulated in part by the integrated stress response (ISR) that regulates cellular responses to a wide variety of stress inducers. A key regulator of the ISR apoptotic response is activating transcription factor 3 (ATF3) and its target gene CHOP/GADD153. In our study, we demonstrate that in multiple lovastatin‐resistant clones of the squamous cell carcinoma (SCC) cell line SCC9, lovastatin treatment (1‐25 μM, 24 hr) in contrast to the parental line failed to significantly induce ATF3 expression. Furthermore, the SCC‐derived cell lines SCC25 and HeLa that are sensitive to lovastatin‐induced apoptosis also preferentially induce ATF3 expression compared to resistant breast (MCF‐7) and prostate carcinoma (PC3)‐derived cell lines. In HeLa cells shRNA targeting ATF3 expression as well as in ATF3‐deficient murine embryonic fibroblasts, lovastatin‐induced cytotoxicity and apoptosis were attenuated. In ex vivo HNSCC tumors, lovastatin also induced ATF3 mRNA expression in two of four tumors evaluated. Salubrinal, an agent that can sustain the activity of a key regulator of the ISR eIF2α, further increased the expression of ATF3 and demonstrated synergistic cytotoxicity in combination with lovastatin in SCC cells. Taken together, our results demonstrate preferential induction of ATF3 in lovastatin‐sensitive tumor‐derived cell lines that regulate lovastatin‐induced apoptosis. Importantly, combining lovastatin with salubrinal enhanced ATF3 expression and induced synergistic cytotoxicity in SCC cells. Abstract : What's new? While statins hold promise in the fight against cancer, owing to their ability to inhibit the growth and metastatic potential of tumor cells, clinical studies have yielded conflicting results. This study offers a possible explanation for differences in clinical findings, revealing that activation of transcription factor 3 (ATF3) regulates the apoptotic response induced by lovastatin in lovastatin‐sensitive, tumor‐derived cells. Salubrinal, an agent capable of prolonging the activity of stress‐induced ATF3 expression, enhanced lovastatin‐induced cytotoxicity. The results suggest that ATF3 inducers, in combination with agents such as lovastatin or salubrinal, could improve clinical response.